Direct Growth of Polyaniline Chains from N‐Doped Sites of Carbon Nanotubes. Issue 22 (2nd May 2013) - Haq, Atta Ul; Lim, Joonwon; Yun, Je Moon; Lee, Won Jun; Han, Tae Hee; Kim, Sang Ouk
Abstract Polymer grafting from graphitic carbon materials has been pursued for several decades. Unfortunately, currently available methods mostly rely on the harsh chemical treatment of graphitic carbons which causes severe degradation of chemical structure and material properties. A straightforward growth of polyaniline chain from the nitrogen (N)‐doped sites of carbon nanotubes (CNTs) is presented. N‐doping sites along the CNT wall nucleate the polymerization of aniline, which generates seamless hybrids consisting of polyaniline directly grafted onto the CNT walls. The resultant materials exhibit excellent synergistic electrochemical performance, and can be employed for charge collectors of supercapacitors. This approach introduces an efficient route to hybrid systems consisting of conducting polymers directly grafted from graphitic dopant sites.